Functional Roles of the IgM Fc Receptor in the Immune System - Kubagawa, Hiromi; Honjo, Kazuhito; Ohkura, Naganari; Sakaguchi, Shimon; Radbruch, Andreas; Melchers, Fritz; Jani, Peter K. (Frontiers in Immunology, 2019)
It is now evident from studies of mice unable to secrete IgM that both non-immune “natural” and antigen-induced “immune” IgM are important for protection against pathogens and for regulation of immune responses to self-antigens. Since identification of its Fc receptor (FcµR) by a functional cloning strategy in 2009, the roles of FcµR in these IgM effector functions have begun to be explored. Unlike Fc receptors for switched Ig isotypes (e.g., FcγRs, FcεRs, FcαR, Fcα/µR, pIgR, FcRn), FcµR is selectively expressed by lymphocytes: B, T, and NK cells in humans and only B cells in mice. FcµR may have dual signaling ability: one through a potential as yet unidentified adaptor protein non-covalently associating with the FcµR ligand-binding chain via a His in transmembrane segment and the other through its own Tyr and Ser residues in the cytoplasmic tail. FcµR binds pentameric and hexameric IgM with a high avidity of ~10 nM in solution, but more efficiently binds IgM when it is attached to a membrane component via its Fab region on the same cell surface (cis engagement). Four different laboratories have generated Fcmr-ablated mice and eight different groups of investigators have examined the resultant phenotypes. There have been some clear discrepancies reported that appear to be due to factors including differences in the exons of Fcmr that were targeted to generate the knockouts. One common feature among these different mutant mice, however, is their propensity to produce autoantibodies of both IgM and IgG isotypes. In this review, we briefly describe recent findings concerning the functions of FcµR in both mice and humans and propose a model for how FcµR plays a regulatory role in B cell tolerance.